(untitled) (Research, Society and Development, 2022)
Salivary gland tumors, although uncommon, are not uncommon. Given its location, it is difficult to correctly diagnose these pathological changes only with the use of clinical examination. Complementary exams such as ultrasonography (US) should be used, which must be safe and accurate. Thus, the aim of this study was to describe the accuracy of US for the diagnosis of salivary gland tumors compared to histopathological evaluation. This is an integrative review. Searches were carried out in the PUBMED/MEDLINE, Scopus and Embase databases, using the following descriptors in English: “ultrasonography/ultrasound”; “salivary glands”; “lesions”; “cyst” and “tumour”. Six articles published from 2015 to 2017. It was verified that the main salivary gland tumors identifiable by means of US are pleomorphic adenoma and Warthin’s tumor and that these mainly affect the parotid gland. Studies showed mean accuracy values ​​ranging from 73.1% to 93.4%, sensitivity from 60% to 80%, specificity from 76.9% to 92.0%. Characteristics such as lesion size, echogenicity, regularity of the margin and vascularity were mentioned as standard for diagnosis of lesions. Thus, US is a promising resource for the diagnosis of salivary gland tumors, since it is an accurate imaging test compared to histopathological examination, non-invasive, painless and with high specificity in soft tissues. However, it is operator-dependent and the professional’s experience can influence the interpretation of images.